Parental awareness and dental health behavior of children with congenital heart disease, with diabetes mellitus, or undergoing anti-cancer treatment, compared to healthy children - Halperson, Elinor; Badarneh, Hanan; Zion, Ella; Kruchenezki, Helly; Goldstein, Gal; Gavri, Sagui; Zangen, David; Fux-Noy, Avia (Frontiers in Oral Health, 2024)
IntroductionChildren with chronic diseases tend to experience a considerably higher burden of oral disease compared to their healthy peers. Low awareness of the impact of systemic diseases on oral health, lack of motivation, and discomfort may render the maintenance of good oral hygiene challenging. We conducted a study of four groups of parents: of children with congenital heart disease (CHD), with diabetes mellitus type 1 (DM), and undergoing anti-cancer treatment (ACT); and a control group of healthy children (C). We aimed to compare between the groups, parental attitudes and knowledge of their children's oral health, and their reports of their children's dental habits.MethodsParents who arrived with their children for routine check-ups at three main clinics: cardiology, endocrinology, and hematology-oncology were asked to respond to a questionnaire regarding their children's oral and dental health.ResultsA total of 287 questionnaires were collected from 76 parents of children with CHD, 100 parents of children with DM, 50 parents of children undergoing ACT, and 61 parents who comprised group C. Compared to the CHD and DM groups, the ACT group demonstrated significantly more awareness of the importance of maintaining oral and dental health following diagnosis of their children's medical condition. Mothers’ education was found to correlate with dental health knowledge. Most children in the DM and C groups had previous dental examinations, compared to only half in the CHD and ACT groups. A higher proportion of the children in the C than the other groups brushed teeth twice daily. The groups were similar in their consumption of sugary drinks, and of sweets and snacks. The children's specialist physicians were the main source of information on oral health, especially in the ACT group.ConclusionsAlthough most of the parents reported awareness to the oral health aspects of their children's disease, only part of them reported that their children visited dentists, and brushed their teeth twice daily. For the parents of children with CHD, DM, and ACT, their children's treating specialists were the primary source of information regarding oral health. This highlights the importance of clear and continuous communication between pediatric specialists and dentists.